Lecture Methods and Media Leaflets on Mother's Knowledge in ISPA Prevention - Bidaya, Bohalima (Journal of Health Science and Medical Therapy, 2023)
Acute Respiratory Infection (ARI) is an acute infectious disease that attacks one or more parts of the respiratory tract from the nose (upper tract) to the alveoli (lower tract) including their adnexa such as the sinuses, middle ear cavity and pleura . This study aims to determine the effect of health education using the lecture method and leaflet media on increasing mothers' knowledge about the prevention of ARI (Acute Respiratory Infection) in the work area of the UPT Puskesmas Hiliduho . This type of research is a quantitative research with a quasi-experimental research design. The design used was pretest and posttest group design without control group. The research location was carried out in the working area of the Hiliduho Health Center, Hiliduho District , Nias Regency . When this research was conducted in August 2021. The population in this study totaled 389 people. The sample in this study was determined by purposive sampling technique. The number of samples is 80 people. The difference in mean knowledge of mothers before and after the lecture method health counseling was known to have a significant value from the t test for respondents in the lecture group, namely p = 0.000 (p <0.05). The mean value of the respondent's knowledge before the lecture intervention was 1.98 while the mean value of the respondent's knowledge after the lecture was 1.18. Differences in the average knowledge of mothers before and after the media leaflet health counseling was carried out p=0.000 (p<0.05). The mean value of the respondents' knowledge before the leaflet intervention was 5.68 while the mean value of the respondents' knowledge after the leaflet was 12.90. Therefore it is necessary to provide counseling on an ongoing basis, especially to mothers under five.